Frank Moore Cross and the History of Ancient Israel - Coogan, Michael D. (Bulletin of ASOR, 2014)
This essay examines Frank Moore Cross's reconstructions of ancient Israelite history, focusing on his essays on the tribe of Reuben and on the Judaean restoration, with attention both to his methodology and to his conclusions.